Assessment of the chemical stability of furfural derivatives and the mixtures as fuel components. (1st July 2020) - Tarazanov, Sergey; Grigoreva, Katharine; Shipitcyna, Anastasiia; Repina, Olga; Ershov, Michael; Kuznetsova, Svetlana; Nikulshin, Pavel
Highlights: Furfural derivatives including 2-methylfuran and furfurylamine were considered as fuel additives. Intermediates obtained by furfural hydrogenation over Cu- and Ni based catalysts were studied. The effect of furfural derivatives on octane number of base hydrocarbon fractions was evaluated. Chemical stability was evaluated by means of standardized methods. Fuel compositions with furfural derivatives were proposed. Abstract: Furfural derivatives, prepared from vegetable raw materials, have recently become popular as high-performance fuel additives. Special attention is drawn to such compounds as oxygenates. A lot of research has been conducted into creating new substances from furfural, but it is still unclear how exactly they affect physicochemical properties of fuels. This article will demonstrate the possibility of adding furfural derivatives, obtained by their hydrogenation at copper and nickel catalysts with full furfural conversion, to fuel. Their impact on antiknock properties and chemical stability was evaluated. It was noticed that furans are mostly effective in low-octane bases (gasoline HC) at 5–30% wt. concentration. High concentration of potential gum may lead to carbon depositions in the combustion chamber of an engine that requires additional tests.